Mise-en-scène. Politiche di autorappresentazione e autenticità su YouTube (Mantichora. Italian Journal of Performance Studies, 2020)
YouTube features an exponentially growing collection of video, spoken and audio data that are still unexplored. Handling such data is a challenging undertaking which calls for a multidisciplinary approach, which takes into account the highly complex nature of YouTube texts. This paper sets out to illustrate politics of self-representation and authenticity in a non commercial video on YouTube, with grounding theories provided by systemic-functional grammar (Halliday 1978; Halliday & Mathiessen 2004 [1984]) and methods of enquiry from multimodal corpus linguistics (Baldry & O’Halloran 2010). In particular, a top viewed and top rated non commercial video will be analyzed as a multimodal “mastertext”, originating a wealth of “metatexts”, i.e. written comments. A corpus-driven study of a sample of ca. 70000 comments will provide insights into interactional dynamics within video-sharing communities and, more specifically, explore transitivity patterns with reference to the Hallidayan experiential metafunction. Despite the apparent randomness and breaking of the relevance maxim (Grice 1975) of such comments, a corpus-driven analysis gives evidence for relatively fixed categorizations on the grounds that transitivity patterns are regular and highly predictable. Examples of material, mental and relational processes endorse this heuristic interpretation.